Application for Bankruptcy Declaration or Suspension of Debt Payment Obligation for Developers Viewed from the Principles of Balance and Justice - Faisal, Fedhli (Faculty of Law, Universitas Pekalongan, 2024)
The aim of this research is to examine the implications of bankruptcy petition or postponement of debt payment obligations on developers in Indonesia, considering legal principles, particularly the principles of balance and justice within the framework of the Bankruptcy and Debt Payment Obligation Postponement Act (UU Kepailitan & PKPU). The background of this study encompasses the importance of legal certainty for consumers and developers in the context of fair and efficient financial settlements. The research methodology employs a legal document analysis approach, involving literature review and case interpretation to evaluate the application of the Bankruptcy and PKPU Act on developers, and to analyze the impact of Supreme Court Regulation No. 03/2023 on court interpretations in relevant cases. The findings indicate that the Bankruptcy and PKPU Act provides a crucial legal framework to protect the interests of consumers and developers, but its application must carefully consider legal principles, particularly in proving facts or circumstances influencing decisions on bankruptcy or PKPU petitions. The implications of these findings underscore the need for courts to maintain a balance between creditors' rights and protection for debtors experiencing financial difficulties. Proposed recommendations include the necessity for clarity in legal interpretations, consistent implementation of the Bankruptcy and PKPU Act, and an approach favoring justice in every bankruptcy or PKPU petition decision.